Performance of timed function tests as outcome measures in idiopathic inflammatory myopathy—results from a single-centre cohort. (13th April 2022) - Dunga, Saikumar; Kavadichanda, Chengappa; Bairwa, Devender; Thabah, Molly Mary; Negi, Vir Singh
Abstract: Objective: To evaluate performance of timed function tests (TFTs) in assessing muscle strength and endurance as determined by Manual Muscle Testing 8 (MMT-8) and Functional Index 2 (FI-2), respectively, in idiopathic inflammatory myopathies (IIM). Methods: This cohort study included 42 IIM patients satisfying 2017 EULAR/ACR criteria. Patients were classified as active ( n  = 18) or inactive disease ( n  = 24) based on clinical status at baseline. MMT-8, FI-2, 30 s rise from chair test, 30 s 1 kg arm rise test and 2-min walking distance (2MWD) were administered at baseline, 3 months and 6 months. Pearson rank correlation analysis and receiver operating curves were performed to assess the performance of timed function tests. Results: All patients were followed up at 3 months and 39 completed 6 months' follow-up. All the three TFTs had excellent convergent (r > 0.7, P  < 0.05) and divergent validity ( P  < 0.05). Only 2MWD had moderate to strong correlation with ΔMMT-8 at 3 and 6 months among those with active disease ( P  = 0.001). All the TFTs correlated with ΔFI-2 in active disease but only Δ2MWD correlated with ΔFI-2 in inactive disease at 6 months (r = 0.506, P  = 0.036). At a cut-off of 5% improvement in MMT-8, 2MWD had an area under the curve (AUC) of 0.868 with 95% sensitivity with 2% improvement at 3 months. To detect a 10% ΔMMT-8, Δ2MWD at a cut of 8% and 7% had an AUC of 0.909 and 0.893 with a sensitivity of 92% at 3 and 6 months, respectively ( P  < 0.05). Conclusion: 2MWD is a reliable indicator of muscle strength, endurance and treatment response. The 2MWD can be self-administered by patients, making it a potential patient-reported outcome measure.